The Effect of Scoliosis Orthosis on the Reduction of Cobb Angle in Scoliosis Patients: A Meta-Analysis - Suprayogi, Dody; Kristiyanto, Agus; Prasetya, Hanung (Indonesian Journal of Medicine, 2020)
Background: Scoliosis is a spinal deformity that often occurs in adolescents with a prevalence of 0.47% -5.2% worldwide. The prevalence of scoliosis in Asia was about 2.25% of the population. In Surabaya, Indonesia, 6.37% of students from 784 schools who conducted scoliosis screening tests positively had scoliosis. In addition, 9 out of 300 students in Surakarta positively had scoliosis. This study aimed to estimate the effect of using scoliosis orthosis in reducingcobb angle in scoliosis patients by conducting a meta-analysis on theseveral similar articles.Subjects and Method: This study used a meta-analysis by systematically reviewing the several similar articles from PubMed, ScienceDirect, and Google Scholar. The keywords were "scoliosis" AND "scoliosis orthosis" OR "scoliosis brace" AND "cobb angle" OR "curve" AND "randomized control trial". The intervention was the use of a scoliosis orthosis with a comparison of non-scoliosis orthosis and the scoliosis patients as the study subjects. The outcome of the study was a reduction of cobb angle. The included articles were full-text articles with a randomized controlled trial design that showed the effect size (mean and standard deviations). The articles were collected using PRISMA flow diagrams and analyzed using the Review Manager 5.3 application.Results: Based on a meta-analysis result of 9 randomized controlled trial articles from the United States, Canada, Germany, Sweden, Denmark, Poland, and Hong Kong, scoliosis orthosis reduced cobb angle in scoliosis patients (SMD= -0.67; 95% CI= -1.02 to -0.33; p <0.001). The heterogeneity I2=75%.Conclusion: Scoliosis orthosis affects the reduction of cobb angle in scoliosis patients.Keywords: scoliosis, cobb angle, scoliosis orthosisCorrespondence: Dody Suprayogi. Masters Program in Public Health. Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: 23dhodik.yogi@gmail.com. Mobile: 08562772052.Indonesian Journal of Medicine (2020), 05(04): 356-367https://doi.org/10.26911/theijmed.2020.05.04.11.